The Forces Driving Streaming in the Presence of Scatterers Mimicking the Blood Cells and the Contrast Agents - WÓJCIK, Janusz; SECOMSKI, Wojciech; ZOŁEK, Norbert (Archives of Acoustics, 2019)
Acoustical Driving Forces (ADF), induced by propagating waves in a homogeneous and inhomogeneous lossy fluid (suspension), are determined and compared depending on the concentration of suspended particles. Using integral equations of the scattering theory, the single particle (inclusion) ADF was calculated as the integral of the flux of the momentum density tensor components over the heterogeneity surface. The possibility of negative ADF was indicated. Originally derived, the total ADF acting on inclusions only, stochastically distributed in ambient fluid, was determined as a function of its concentration. The formula for the relative increase in ADF, resulting from increased concentration was derived. Numerical ADF calculations are presented. In experiments the streaming velocities in a blood-mimicking starch suspension (2 μm radius) in water and Bracco BR14 contrast agent (SF6 gas capsules, 1 μm radius) were measured as the function of different inclusions concentration. The source of the streaming and ADF was a plane 2 mm diameter 20 MHz ultrasonic transducer. Velocity was estimated from the averaged Doppler spectrum obtained from originally developed pulsed Doppler flowmeter. Numerical calculations of the theoretically derived formula showed very good agreement with the experimental results.